Seroprevalence of Ehrlichia canis in Dogs with Suspected Infection by Tick-Borne Pathogens in Medellín, 2012-2014 - Cartagena Yarce, Lina María María (Universidad de La Salle. Revistas. Revista de Medicina Veterinaria., 2015)
Research is meager on canine ehrlichiosis in Colombia and it is absent in Medellín. This research aims to determine the seroprevalence of Ehrlichia canis and its distribution by sex, age, race and size in dogs diagnosed in a veterinary laboratory in Medellín, between 2012 and 2014. To the effect, a cross-sectional study was designed in 781 dogs. Overall seroprevalence of infection and specific by sex, age, size, and canine breed were calculated. In the bivariate analysis, Z test, Pearson’s chi-square test, and the Mann-Whitney U test were used. In the multivariate analysis, binary logistic regression was performed. 57 races were included, of which the most frequent were Creoles, Labradors, and French poodles; 54.9% were males, and 56.9% were adults. Overall prevalence of infection was 24.8%; highest specific seroprevalences were observed in females (25.9%), senile dogs (29.7%), and those belonging to large breeds (27.6%). The risk of infection in adult and senile dogs was two times higher than in puppies; the probability of infection was 6.4 times higher in cocker spaniels than in French bulldogs; the risk of infection in Siberian wolf, pug and Labrador was 7.8, 5.5 and 4.1 times higher than in bulldogs. High seroprevalence of canine ehrlichiosis and the identification of adult and senile dogs, and cocker spaniel, Siberian wolf, pug and Labrador breeds as of higher risk show the need to develop programs for prevention and treatment of this infection in the city.